Implementation of hybrid filter technique for noise removal from medical images - Choubey, Shruti Bhargava; Subba Rao, S.P.V. (International Journal of Engineering and Technology, 2017)
Image denoising is used to eliminate the noise while retaining as much as possible the important signal features. The function of image denoising is to calculate approximately the original image form the noisy data. Image denoising still remains the challenge for researchers because noise removal introduces artifacts and causes blurring of the images. Image denoising has become an essential exercise in medical imaging especially the Magnetic Resonance Imaging (MRI). MR images are typically corrupted with noise, which hinder the medical diagnosis based on these images.Â The presence of noise not only causes as undesirable visual quality as well as lowers the visibility of low contrast objects. in this paper noise removal approach has proposed using hybridization of three filter with DWT method.Results calculated in terms of PSNR,MSE & TIME.